Use, physiology and genetic characterisation of selected natural populations of Adansonia Digitata in Malawi - Munthali, Chimuleke Rowland Yagontha (Stellenbosch : Stellenbosch University, 2011)
Thesis (PhD For) (Forest and Wood Science))--Stellenbosch University, 2012.